2009
DOI: 10.1002/art.24392
|View full text |Cite
|
Sign up to set email alerts
|

Defining remission in rheumatoid arthritis: Results of an initial american college of rheumatology/european league against rheumatism consensus conference

Abstract: Objective. Due to advances in rheumatoid arthritis (RA) therapies over the last few years, an increasing proportion of patients are able to achieve a state of remission. However, the definition of remission is unclear. Currently, randomized controlled trials around the world use different remission definitions and consequently measure different aspects of a patient's disease state. The need for a uniform definition of remission is vital for research findings to be correctly interpreted. Methods. The American C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
(31 reference statements)
1
49
0
4
Order By: Relevance
“…The classification of RA fulfilled the 1987 and 2010 American College of Rheumatology criteria (13,14). RA patients were divided into active (n = 26) and inactive (n = 23) groups, according to their 28-joint disease activity score (DAS28); active disease is defined as DAS28 $ 3.2, based on the European League Against Rheumatism diagnostic criteria (15). At the time of sample acquisition, 38 patients were being treated with prednisone, and 11 patients were not.…”
Section: Patients and Hcsmentioning
confidence: 99%
“…The classification of RA fulfilled the 1987 and 2010 American College of Rheumatology criteria (13,14). RA patients were divided into active (n = 26) and inactive (n = 23) groups, according to their 28-joint disease activity score (DAS28); active disease is defined as DAS28 $ 3.2, based on the European League Against Rheumatism diagnostic criteria (15). At the time of sample acquisition, 38 patients were being treated with prednisone, and 11 patients were not.…”
Section: Patients and Hcsmentioning
confidence: 99%
“…Although recent advances in treatment have led to an increase in the proportion of patients reaching a state of remission 22 there is no "gold standard" measurement of disease activity and remission in RA 4 . Numerous pooled indices have been developed to measure disease activity, each of which incorporates 3-10 different assessments 23,24,25,26,27,28,29,30,31 .…”
Section: Assessments For Standard Clinical Carementioning
confidence: 99%
“…Indeed, a recent study in which patients' disease activity was assessed by different indices (including DAS28, SDAI, and CDAI) demonstrated that different proportions of patients were found to be in remission depending on the definition used 42 ; further comparisons of disease activity indices are therefore required. A collaborative committee between ACR and EULAR has been convened to develop a strict definition of remission that correlates with very low or no disease activity 22 .…”
Section: Domentioning
confidence: 99%
“…Acute phase reactants were included as one of the 3 most important variables, beside tender and swollen joint counts, in defining remission of RA at initial ACR/EULAR Consensus Conference (van Tuyl, Vlad et al 2009) and normal CRP and ESR levels are one of the three criteria defining disease inactivity in juvenile RA. Patients with 25 very active RA had significantly higher SAA levels in the serum than 23 patients with moderately/mildly active or inactive disease (Maury, Teppo et al 1982).…”
Section: Apps During Ra Disease Stagesmentioning
confidence: 99%